Delayed and limited administration of the JAKinib tofacitinib mitigates chronic DSS-induced colitis - Seal, Rishav; Schwab, Lara S. U.; Chiarolla, Cristina M.; Hundhausen, Nadine; Klose, Georg Heinrich; Reu-Hofer, Simone; Rosenwald, Andreas; Wiest, Johannes; Berberich-Siebelt, Friederike (Frontiers in Immunology, 2023)
In inflammatory bowel disease, dysregulated T cells express pro-inflammatory cytokines. Using a chronic azoxymethane (AOM)/dextran sulfate sodium (DSS)-induced colitis model resembling ulcerative colitis, we evaluated whether and when treatment with the Janus kinase (JAK) inhibitor tofacitinib could be curative. Comparing the treatment with two and three cycles of tofacitinib medication in drinking water – intermittently with DSS induction – revealed that two cycles were not only sufficient but also superior over the 3-x regimen. The two cycles of the 2-x protocol paralleled the second and third cycles of the longer protocol. T cells were less able to express interferon gamma (IFN-γ) and the serum levels of IFN-γ, interleukin (IL)-2, IL-6, IL-17, and tumor necrosis factor (TNF) were significantly reduced in sera, while those of IL-10 and IL-22 increased under the 2-x protocol. Likewise, the frequency and effector phenotype of regulatory T cells (Tregs) increased. This was accompanied by normal weight gain, controlled clinical scores, and restored stool consistency. The general and histologic appearance of the colons revealed healing and tissue intactness. Importantly, two phases of tofacitinib medication completely prevented AOM-incited pseudopolyps and the hyper-proliferation of epithelia, which was in contrast to the 3-x regimen. This implies that the initial IBD-induced cytokine expression is not necessarily harmful as long as inflammatory signaling can later be suppressed and that time-restricted treatment allows for anti-inflammatory and tissue-healing cytokine activities.